Construção de um questionário para análise do conhecimento sobre o atendimento inicial ao queimado - Balan, Marli Aparecida Joaquim (2008)
Health teams providing initial assistance for burn victims must have scientific knowledge in order to increase the chances of survival for these patients. Given there is no nationwide standard to evaluate the knowledge of health professionals on this specialty, the objective of this study was to build a tool to measure and identify the knowledge of nurses and physicians regarding initial assistance for burn victims. This is a methodological research with a quantitative approach. Authorization was obtained from The Committee for Ethics and Human Research, and from the teaching hospital where the pre-test was conducted. The creation of the validation instrument was based on Pasquali's theory of psychological scales (1998) and consisted of theoretical solving, by means of the investigation of authoritative references in the nursing and medical fields, and construction of sixty multiple choice questions. Apparent validity and content were analyzed by means of an evaluation by an eight-member panel of experts and ten health professionals, respectively, as wel las by a pre-test at the teaching hospital ER. The experts, based on the "Analytical guide of the psychometric properties of the questionnaire (adapted from Pasquali, 1998)" presented thirty-six questions with content validity. The ten health professionals made suggestions, which were accepted, to improve the intelligibility of the questions. The validated tool consisted of thirty-seven questions about the initial assistance for burn victims, approaching general knowledge, nursing and medicine. The questionnaire was applied on a sample of 21 nurses and 22 physicians. They were distributed equally between males and females, with average age of 38 years; 25 (58,1%) had specialization degrees, 12 (27,9%) had Masters Degrees, five (11,6%) had PhDs, and one (2,3%) had only bachelor degrees. Four nurses and nine doctors declared they learned more on burns from courses/training discussions/scientific meetings and/or events symposiums, at libraries, reading books and articles, and on the Internet. In order to verify the internal consistency of the general knowledge questionnaire, questions 2, 3 and 9 were discarded through biserial correlation because they were not correlated with the construct. The other seven had similar parameters through Response Theory for item "a", showing that this instrument does not discriminate against responders; as for difficulty, "b", the items are varied with parameters between -1,3 and 1,2; the probability of random guessing, "c", is also approximately equal. Thus, the general knowledge analysis tool was calibrated, but with high standard deviation, because the sample size was not sufficient to satisfactory estimate the model's parameters. The validation of this instrument contributes to quantify the knowledge that health professionals hold in this field. Thus study will support educational interventions to improve professional training in this field. The importance of further studies is emphasized to determine the reliability of this instrument.